2021
DOI: 10.1186/s13045-021-01044-y
|View full text |Cite
|
Sign up to set email alerts
|

CD19 CAR-T expressing PD-1/CD28 chimeric switch receptor as a salvage therapy for DLBCL patients treated with different CD19-directed CAR T-cell therapies

Abstract: CD19-targeted chimeric antigen receptor T (CAR T) cell therapy is a promising option to treat relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). However, the majority of CAR T-treated patients will eventually progress and require salvage treatment, for which there is no current standard. In this study, we analyzed data from 6 patients with R/R DLBCL who experienced progression following CD19-CAR T therapy, and then received CD19-specific CAR T cells that express a PD-1/CD28 chimeric switch-receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…[8][9][10][11] Moreover, in clinical trials, the application of the PD1-28 chimera presented encouraging results. 48 The Carl June group verified that the co-stimulatory domain 41BB promotes memory T cells and CD28 promotes effector T cells. In this study, our data showed that T3-CD28 signaling combined with 41BB might benefit CAR-T cells to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Moreover, in clinical trials, the application of the PD1-28 chimera presented encouraging results. 48 The Carl June group verified that the co-stimulatory domain 41BB promotes memory T cells and CD28 promotes effector T cells. In this study, our data showed that T3-CD28 signaling combined with 41BB might benefit CAR-T cells to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…To further verify the effects of 7 × 19 secretion on human CAR-T cells, we constructed three CAR vectors targeting GPC3, MSLN, and CD20 (Fig. 1a) [4][5][6], which all contained intracellular domains of CD28 and TLR2 [7][8][9]. As the cargo capacity of the lentiviral vector is limited, human IL-7 and CCL19 linked through the 2A peptide were inserted into a separate lentiviral vector (Fig.…”
Section: To the Editormentioning
confidence: 99%
“…8 Guangdong Zhaotai Cell Biology Technology Ltd., Guangzhou, China. 9 Guangdong Zhaotai InVivo Biomedicine Co. Ltd., Guangzhou, China. 10 The Second Xiangya Hospital, Central South University, Changsha, China.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Both the PD-1/CD28 CSR and the IL-4/7 ICR should be combined ( Figure 8C ). After being activated, CAR-T cells expressing these two receptors may be able to reverse the inhibitory signal transmitted by tumor cells as well as the inhibitory effect of IL-4 simultaneously ( 29 , 32 , 34 37 ).…”
Section: Improving the Killing Ability Of Carsmentioning
confidence: 99%